2015
DOI: 10.15713/ins.jcri.37
|View full text |Cite
|
Sign up to set email alerts
|

Educational intervention on the plaque score among hearing impaired children

Abstract: Background: Oral health is an integral part of overall health of all children. The maintenance of oral health of hearing impaired children is a challenging problem; due to lack of communicative skills and access to dental care. There is a need to improve oral health of children with hearing impairment (CHI). The aim is to evaluate the impact of oral health education (OHE) intervention on the plaque scores among hearing impaired children. Materials and Methods: A total of 56 institutionalized CHI aged range 5-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
(18 reference statements)
1
12
0
Order By: Relevance
“…Training on oral hygiene practices should be given on daily basis to achieve desired benefits of the technique demonstrated to them in the study. When an educational intervention among hearing impaired children was carried out in a study conducted by Alse et al [16] it showed higher plaque score before oral health education in children with hearing impairment, similar to earlier studies. [17][18][19][20][21] In the present study, the females showed higher score when the mean of plaque and gingival index was considered in both control and experimental group, prior and post intervention.…”
Section: Discussionsupporting
confidence: 75%
“…Training on oral hygiene practices should be given on daily basis to achieve desired benefits of the technique demonstrated to them in the study. When an educational intervention among hearing impaired children was carried out in a study conducted by Alse et al [16] it showed higher plaque score before oral health education in children with hearing impairment, similar to earlier studies. [17][18][19][20][21] In the present study, the females showed higher score when the mean of plaque and gingival index was considered in both control and experimental group, prior and post intervention.…”
Section: Discussionsupporting
confidence: 75%
“…After adding additional 7 records identified by hand and grey literature searching, a total of 24 publications were judged to meet the inclusion criteria and their data were extracted (Figure 1). 18 reported from 11 different countries: Bulgaria, 22 Egypt, 23,24 India, 11,12,[25][26][27][28][29][30][31][32][33] Indonesia, [34][35][36] Iran, 37 Malaysia, 38 Mexico, 39 Pakistan, 40 Saudi Arabia, 41 Thailand 42 and the United Arab Emirates (UAE). 43 Most of the studies were conducted in the last decades and included three types of study designs including randomized trials, 11,12,23,[25][26][27]37,[40][41][42][43] non-randomized trials, 28,29,33,34,36 and pre-post intervention without control studies.…”
Section: Resultsmentioning
confidence: 99%
“…43 Most of the studies were conducted in the last decades and included three types of study designs including randomized trials, 11,12,23,[25][26][27]37,[40][41][42][43] non-randomized trials, 28,29,33,34,36 and pre-post intervention without control studies. 22,24,[30][31][32]35,38,39 Randomized controlled trials were further divided into parallel trials, 11,12,23,26,37,[40][41][42] cluster trials 25,27 as well as cross-over trials. 43 The age in included studies ranged between 5 years and 20 years and the sample size ranged between 15 and 372 hearing impaired children or adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…The plaque index (TQHI) is a site-related plaque scoring method used in the present study for comparing toothbrush efficacy, it was well suited for recording interproximal plaque in children according to Bezgin, those who have abundant gingival papillae in interproximal areas have an advantage of clear objective definitions of each numerical score included in the index. 4 Alse et al 10 also assessed the oral hygiene status using the TQHI and found it to be effective. For recording the gingival index score, the gingival index system as proposed by Loe and Silness was used, which is entirely confined to qualitative changes in the gingival soft tissues.…”
Section: Discussionmentioning
confidence: 99%